Pengaruh Eksploitasi Sumber Daya Alam Perairan Terhadap Kemiskinan Pada Masyarakat Nelayan - Feryl Ilyasa; Muhammad Zid; Mieke Miarsyah (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
The aim of this article is to find out how the influence of exploitation of aquatic natural resourceson the poverty of fishing communities. The method in this article used a descriptive research design forusing a literature study approach. Based on the type of research and the type of data source used, the datacollection technique in this study is used the secondary data. The results in this study can be seen in twoaspects, are: (1) the ease of foreign investments that can be exploit for the natural resources of fisheries inIndonesia; (2) the influence of exploitation of the natural resources of the waters carried out on poverty inthe fisihing community. Exploitation of aquatic natural resources in Indonesia is due to the ease with whichforeign parties can be invest in Indonesia in the field of fisheries, and then this ease of investment fromforeign parties results in the intervention of foreign parties who can to control the natural waters resourcesin Indonesia, both in the form a legal entitiy or in the form of an individual, it can be also for drain thenatural waters resources, especially fisheries in Indonesia, and which can to be affect the walfare of fishingcommunities.